A review on the microbiology of Ethiopian traditional fermented beverage products - Mulaw, Guesh; Gebregziabher, Trhas; Tesfay, Teklemichael (Frontiers in Nutrition, 2025)
Traditional fermented beverages are drinks produced locally on the basis of ethnic knowledge and consumed nearby the locality of production. Ethiopia is a country where a wide variety of traditional fermented beverages are prepared and consumed. Tella, borde, shamita, korefe, cheka, tej, booka, grawa, areki, and keribo are among the traditional fermented beverages in Ethiopia. This review paper highlights the fermentation process and nutritional value of traditional fermented beverages, microorganisms involved in the traditionally ferreted beverages, the nutritional value and shelf-life of fermented beverages, as well as the bioavailability and safety by collecting recent research articles. These traditional fermented beverages significantly enhance health due to the presence of bioactive compounds and their nutritional value relatively greater than those of nonfermented beverages. The fermentation byproducts of yeast and Lactic Acid Bacteria (LAB) increase the acidity of beverages and are crucial for maintaining the quality and characteristics of fermented beverages. It also helps to reduce the amount of toxins and pathogens in food. Similarly, fermented foods contain probiotics, which are beneficial bacteria that help the body to digest food and absorb nutrients. The fermented foods and beverages are important in preventing non-communicable diseases such as cardiovascular diseases, gastrointestinal tissues, immune disorders, and cancer. Overall, the paper provides a comprehensive overview of the current knowledge and tradition on Ethiopian fermented beverages.